The Phenomenon of Information Overload in Decisional Management Processes - Światowiec-Szczepańska, Justyna (Studia Oeconomica Posnaniensia, 2018)
The main objective of the paper is to assess the importance of information overload phenomenon in the context of managerial strategic decision making and to explore the usefulness of known decision making theories in conditions of information overload. The considerations in the paper are conceptual in nature. The first part of the article describes the essence and causes of information overload. The next part focuses on the results of research obtained in various disciplines concerning the problem of information overload and, above all, its impact on the decisions made. In the following part, the most important theories of decision making are indicated. Particular attention was paid to the theory of H. Simon. The final problem addressed in the paper are trends that surround the ways in which managers react to the situation of information overload.